Clozapine Treatment for Impulse Control Disorders in Parkinson's Disease Patients: A Case Series. Issue 3 (4th June 2015) - Liang, John; Groves, Mark; Shanker, Vicki L.
Abstract: Impulse control disorders (ICDs) are nonmotor complications of dopaminergic medications characterized by problems in behavioral self‐control. Common management involves discontinuing or lowering dopaminergic medication, often producing motor worsening. We performed a retrospective chart review of Parkinson's disease (PD) patients treated with clozapine for ICDs. Four patients treated with clozapine for ICD were identified. Three patients were men. All 4 took dopaminergic medications at the time that ICDs developed; all received dopamine agonist therapy. ICDs included compulsive shopping, binge drinking, and hypersexuality. All 4 patients had complete resolution of symptoms while taking clozapine (12.5–37.5 mg). Two patients discontinued clozapine because of side effects. Larger studies are needed to further evaluate clozapine's role in treating PD patients with ICD.